Ownership concentration, ownership identity and seasoned equity offerings probabilities: Evidence from Germany - Joachim Rojahn; Florian Zechser (Journal of Business Finance & Accounting, 2021)
This study analyzes the effect of ownership concentration and ownership identity on the probability of seasoned equity offerings (SEOs) in the German stock market. In Germany, equity issues require shareholder approval by a supermajority vote of 75% at shareholder meetings. This study contributes to the literature by testing the non-monotonic effect of ownership concentration on the SEO probability. While low levels of ownership concentration can be expected to increase SEO probabilities, for example, through signaling effects, high levels of ownership concentration beyond the 25% blocking minority imply a negative effect, likely driven by the largest shareholder's willingness to maintain control. After constructing a control group using propensity score matching, we find that SEO likelihood is positively affected by the ownership concentration of the largest shareholder, as long as the 25% blocking threshold is not reached, regardless of the largest shareholder's identity. However, once this threshold is exceeded, the SEO likelihood decreases significantly as the equity stake of the largest shareholder increases. Nonetheless, when we control for the identity of the owners with equity stakes above the 25% threshold, the negative effects are predominantly not statistically significant at common levels.
Keywords: 650; blocking minority; endogeneity; German stock market; investor identity; largest shareholder; logistic regression; non-monotonic relationship; propensity score matching; seasoned equity offering; shareholder approval